Learning Strategies Used by Students of Chemical Engineering of UMS to Learn Materials in English - Nurvitasari, Deby Selvia Rahmat, Mauly Halwat Hikmat, Ph. D., Nur Hidayat, M. Pd (2016)
This research is aimed at showing the differences of learning strategies used by high and low achiever students of Chemical Engineering of Muhammadiyah University of Surakarta. The subjects of the research are six students, three of them are high achiever students and the three others are low achiever students. This research is done by classifying the data using the learning strategies classification conducted by O'Malley and Chamot. The type of this research is case study. The data are obtained from the interview and document to the subjects. The result of this research shows that the subjects use various learning strategies classified by O'Malley and Chamot in learning materials in English. Those learning strategies used by the subjects are similar and the others are not. Although they use same strategies, some of those strategies are implemented differently. The differences of learning strategy used by the subjects are in metacognitive and cognitive strategies. The learning strategies that are only used by high achiever students are: advance organization (metacognitive strategies), grouping, auditory representation, and transfer (cognitive strategies). The other learning strategies are used by both high achiever and low achiever students, even by one student of each achiever. Beside the differences in learning strategies used by high achiever and low achiever students above, there are some strategies that are implemented differently by those subjects. The differences in implementation can be seen in metacognitive strategies (organizational planning, self-monitoring, self-evaluation, and self-management), in cognitive strategies (resourcing and elaboration), and both of the socioaffective strategies.